IMPLEMENTING BUILDING INFORMATION MODELLING (BIM) FOR CONTROLLING COST OVERRUN IN CONSTRUCTION PROJECTS - Kai Chen, Goh; Mohammed Yahya, Al-Amri; Gui, Hun Chuen; Sulzakimin, Mohamed; Md Asrul Nasid, Masrom; Toh, Tien Choon (Construction Research Institute of Malaysia (CREAM), 2022)
Hitherto, the construction industry has been the most important contributors to the socioeconomic development of a nation. Around 46.8 percent of public sector projects and an even more worrisome 37.2 percent of projects in private sector were completed on time and within budget. In the past, few studies have focused on the implementation of BIM as an effective cost control initiative undertaken by Malaysian contractors, particularly those whose operations were concentrated in the central region. Consequently, this study aims to address this gap with three distinct objectives: first, to investigate the issues of cost overrun in construction projects that BIM is capable of intercepting; second, to investigate current practises in addressing cost overrun; and third, to identify the use of BIM to control cost overrun issues in construction projects. In order to collect empirical evidence, questionnaires were distributed to 331 CIDB G7 contractors registered in the Kuala Lumpur region; 104 of these contractors responded, giving this study a respectable sampling response rate of 31 percent This study's findings provide evidence that there is broad consensus regarding the causes of cost overruns that BIM can prevent. In addition, this study has successfully uncovered the practises currently utilised by contractors to control construction project cost overruns. Lastly, it has been observed that the adoption and implementation of BIM technology has a significant impact on preventing project cost overruns.